A Child in the Axiological Space - Kunicka, Małgorzata (INSTED: Interdisciplinary Studies in Education & Society, 2017)
An axiological experience of a child at the level of intellect, will and emotions is organised by adults who are important in the child?s life. The personalistic vision of man proposed in this paper ? as the most convincing from the point of view of the child?s personal development ? accepts the personal dignity and the empowerment of a child as unquestionable values but does not assume the equal status of a child and adults in the context of axiological choices, i.e. it does not respect the absolutisation of freedom. A child collects the behaviour patterns which are offered by adults who have axiological reflective consciousness in contrast to a child who functions at the level of axiological emotional awareness. Therefore, the presence of authority figures and personality patterns is indispensable in the educational process.